Clinical and Functional Outcomes of Total Knee Replacement in Osteoarthritic Knees - Kandel, Manoj; Banjade, Deepak; Thapa, Shrawan Kumar; Neupane, Kabin; Adhikari, Sushan (Nepal Orthopaedic Association Journal, 2024)
Introduction: The gold standard, effective treatment for high-grade osteoarthritis of knees is total knee arthroplasty (TKA). Surgical results are excellent, with favorable early postoperative health-related quality of life. Ease of daily activities of living after TKR was evaluated using clinical and functional scores. Methods: Analysis of 42 cases with end-stage osteoarthritis of the knee who underwent TKA at a tertiary care center over a period of two years was done using prospectively collected data. Clinical and functional outcomes in patients undergoing total knee arthroplasty were evaluated using the Knee Society score, WOMAC Score, Oxford knee score, and SF-36 Questionnaire. The association between functional and clinical scores was also evaluated. Results: The mean preoperative Oxford clinical score (OCS) was 19.86 ±2.49 which increased to a postoperative score of 42.38±1.58 at the end of 6 months. Similarly, the mean preoperative knee functional score (KFS) was 55.86±2.25 which increased to a postoperative score of 77.00±1.67 at the end of 6 months, and the mean pre-operative WOMAC Score of 93.50±3.13 improved to a post-operative score of 49.50±2.82. There was a significant increase in SF -36 SCORE, walking, stair climbing capacity, and quality of life during follow-up at 3-, 6- and 12-month intervals. There was a significant association between knee functional score and Oxford clinical score at every interval. Conclusions: Functional ability with the return to pre-disease state and having pain-free stable mobile joint was achieved with total knee arthroplasty, as reflected by the improvement in the post-op knee clinical score and knee functional score.